2000
DOI: 10.1515/znb-2000-0903
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Magnetic Properties of a (μ-Hydroxo)(μ-Pyrazolato) Dicopper(II) Complex

Abstract: Preparation and magnetic properties of a 3,5-dimethylpyrazolate bridged binuclear copper(II) complex [Qi2(L)(3 ,5 -pyz)] (L = l,3-Bis(2-Hydroxy-5-Chlorosalicylideneamino)propan-2-ol) is reported. The crystal structure determined by X-ray diffraction methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The intradimer Cu(II)Á Á ÁCu(II) distance is equal (1) A A (Cu(2)-Cu(1ii) (ii, 1 þ x; y; z). However, the shortest interdimer contact 2.812 (6) A A has been found between Cu(2i) and neighboring molecule O(5) (i, À1 þ x; y; z). As a result slight asymmetry in copper-oxygen from hydroxide ion is observed, whereas pyrazolate bridges two copper atoms in symmetrical fashion.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The intradimer Cu(II)Á Á ÁCu(II) distance is equal (1) A A (Cu(2)-Cu(1ii) (ii, 1 þ x; y; z). However, the shortest interdimer contact 2.812 (6) A A has been found between Cu(2i) and neighboring molecule O(5) (i, À1 þ x; y; z). As a result slight asymmetry in copper-oxygen from hydroxide ion is observed, whereas pyrazolate bridges two copper atoms in symmetrical fashion.…”
mentioning
confidence: 97%
“…The geometry of the ligand implies the formation of polynuclear [M(pz) 2 ] n [1,2] and low-molecular weight di- [3][4][5][6][7][8][9], tri- [10,11], and tetranuclear [12][13][14] complexes with copper(II). Although there are many examples of binuclear copper(II) complexes with one bridging pyrazolate group and alcoholate or phenolate as another bridging group, [3][4][5][6][7][8][9] discrete binuclear copper(II) complexes with both pyrazolate and hydroxide bridges are unknown. It is worth to notice that cyclic trinuclear compounds with l 3 -OH [10,11] were described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently our research group and others have reported the structural and magnetic characterization of polynuclear copper(II) complexes with Schiff base ligands [15][16][17][18][19][20][21][22][23][24][25][26]. In view of the importance of copper(II) compounds and our interest in the magnetic properties of transition metal complexes, we report here the synthesis, crystal structure and magnetic properties of a new tetranuclear copper(II) complex containing three independent distorted open-cubane core.…”
Section: Introductionmentioning
confidence: 99%
“…In a pre ceding study we have described the prepara tion and magnetism of the dicopper(II) com plex [Cu2(L2)(3 ,5 -prz)], (L2 = l,3-Bis(2-hydroxy-5-chlorosalicylideneamino)propan-2-ol) (2) [12]. Since the antiferromagnetic interaction in 1 (-2J = 440 cm-1 ) was shown to be much stronger than that of 2 (-2J = 164 cm-1 ) we also carried out molecular orbital calculations of the 3,5-dimethylpyrazolate by the ab-initio restricted Hartree-Fock (RHF) method.The interaction between the d or bitals and the HOMO's of the 3,5-dimethylpyrazolate was investigated in order to clarify the influ ence of the second bridging ligand on the super exchange interaction.…”
Section: Introductionmentioning
confidence: 99%